Effect of raw material variation, process variables and device stability on drying process of rambutan (Nephelium lappaceum L.) seed - Ahmad, So'bah; Anuar, Mohd Shamsul; Taip, Farah Saleena; Shamsudin, R. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study was conducted to determine the influence of raw material variation, equipment process variables and device stability on the drying process of rambutan seed using oven and microwave drying equipments. The raw material variations studied were skin colour (yellow and fully red), storage period (fresh and stored) and seed mass (5 and 10 g). The important equipment process variables studied were oven temperature (40 and 60°C) and microwave power (250 and 1000 W).The output power and drying distribution in the drying chamber were studied to examine the device stability. Results indicated that the seed mass, oven temperature and microwave power influenced the drying time. The skin colour and storage period were negatively correlated with drying time due to drying time speculate to relay on time required for moisture removal that associated to initial moisture content and seed mass. It is also observed that the drying time will be shorten if the sample was located at the central of the microwave drying chamber. In contrast, the oven exhibited higher stability compared to microwave due to its ability to provide similar level of heating at each location in the drying chamber. This information will aid researchers and industrial operators to design an effective drying process using microwave and oven thus reducing cost and time.